2022
DOI: 10.4317/jced.59314
|View full text |Cite
|
Sign up to set email alerts
|

Severe infections after teeth removal – are we doing enough in preventing them?

Abstract: Background The present study clarified features and prehospital care in patients with severe infection after teeth removal. Material and Methods Patients who were hospitalized for infection following teeth removal were included in this study. Background variables and infection severity parameters were compared between patients who underwent elective and acute teeth removal prior to hospitalization. Additionally, associations of these variables with antibiotic use were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Currently, however, there are no reports showing that microbial findings would be altered in severe OIs compared to milder infections according to patients' systemic condition, although the proportion of patients with underlying systemic disease has been reported to have increased [2,41]. Our earlier studies have shown that severe OIs occur most often in previously healthy adults [11,42]. Dental procedures including extraction and root canal treatment disrupt the mucosal barrier allowing introduction of mucosal opportunistic bacteria to normally sterile tissue, are local oral risk factors for severe OIs [10,11].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Currently, however, there are no reports showing that microbial findings would be altered in severe OIs compared to milder infections according to patients' systemic condition, although the proportion of patients with underlying systemic disease has been reported to have increased [2,41]. Our earlier studies have shown that severe OIs occur most often in previously healthy adults [11,42]. Dental procedures including extraction and root canal treatment disrupt the mucosal barrier allowing introduction of mucosal opportunistic bacteria to normally sterile tissue, are local oral risk factors for severe OIs [10,11].…”
Section: Discussionmentioning
confidence: 93%
“…Our earlier studies have shown that severe OIs occur most often in previously healthy adults [11,42]. Dental procedures including extraction and root canal treatment disrupt the mucosal barrier allowing introduction of mucosal opportunistic bacteria to normally sterile tissue, are local oral risk factors for severe OIs [10,11]. Furthermore, ineffective early treatment of OI may increase the risk of a severe OI [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation